Analysis of Factors Associated with the Utilization of the Kotabaru Community Health Center in the Era of Primary Care Integration - Satria Tanjung Pura; Syamsul Arifin; Mohamad Isa; Ermina Istiqomah; Endah Labati Silapurna (Newinera Publisher, 2026)
Health constitutes a fundamental investment in both human well-being and economic development. Strengthening the primary healthcare system through the Primary Care Integration (PCI) program has therefore emerged as a national priority aimed at delivering comprehensive, accessible, and affordable services. This study seeks to examine the factors associated with the utilization of the Kotabaru Community Health Center (Puskesmas) in the PCI era, with particular emphasis on the relationships among access to healthcare services, health status, and educational attainment in shaping community health-seeking behavior. Employing a literature review approach based on scientific publications from the past five years, the findings indicate that access to healthcare services in the PCI era extends beyond mere geographical proximity, encompassing affordability, administrative simplicity, and the integration of electronic medical records. These dimensions collectively influence the frequency of community visits. Subjective health status emerges as the most dominant determinant, as the PCI system has effectively shifted service utilization patterns from reactive, curative practices toward continuous, life-cycle-based health risk monitoring. Educational level functions as a critical predisposing factor, shaping health literacy and the cognitive capacity of individuals to navigate the newly implemented cluster-based service system. The utilization of the Kotabaru Community Health Center within the PCI framework is therefore significantly shaped by the interplay between accessibility, risk-based health awareness, and the level of community health literacy in making informed medical decisions.